Media Studies Book - Lusted, David (Routledge, 2013)
Introducing media criticism as well as teaching about the media, in inter-disciplinary and 'across the curriculum' teaching, this is the first critical reference book on the important curriculum initiatives taking place in media education. The core of the book is a collection of essays on key concepts from media studies, including 'language', 'narrative', 'institution', 'audience', 'representation', and 'the production process'. Written by teachers for teachers, these essays organise ideas through classroom activities, with a full listing of teaching materials , resources, agencies, and publications in media education. Contributors: Tim Blanchard, Gill Branston, David Buckingham, Jenny Grahame, Karen Manzi and Allan Rowe, Ben Moore, Gillian Swanson, Adrian Tilley, and Tana Wollen.